Aragonite-detritus laminae thickness in the Dead Sea centre during the past 45 kyr - Yin Lu (PANGAEA, 2019)
We measured the aragonite-detritus laminae couplets spanning the last 45 kyr (MIS3-MIS1) as identified in a deep drilling (Core 5017-1) that was retrieved by the International Continental Scientific Drilling Program (ICDP) in the Dead Sea depocenter during 2010-2011.
Supplement to: Lu, Yin; Bookman, Revital; Waldmann, Nicolas D; Marco, Shmuel (2020): A 45 kyr laminae record from the Dead Sea: Implications for basin erosion and floods recurrence. Quaternary Science Reviews, 229, 106143, https://doi.org/10.1016/j.quascirev.2019.106143